PERAN DAN FUNGSI FILSAFAT ILMU DALAM PERKEMBANGAN ILMU PENGETAHUAN BERLANDASKAN NILAI KEISLAMAN - DARLANA Darliana Sormin (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Science is a provision that is very important for human life because human life requires knowledge to be able to adapt to everything that exists in the surrounding environment. Science is also something that distinguishes creatures that have been created by God, among others, humans and animals, humans themselves are different that is given the potential (reason) that is more than other creatures to be able to master and menumbuhkembangkan science. Therefore, by seeing and knowing that science is something that is very important to have roles and functions in human life. In the life of the prime capital world to be safe and prosperous it must have knowledge, with the human sciences can manage, manage and utilize the natural resources God has created to meet the primary needs of human beings. Therefore humans are called as khlaifah in the earth so that humans can arrange as well as possible for the welfare of mankind. Keywords: Roles, Functions, Philosophy, Science, Development, Science, Values, Islamization